Quest for Unified Identity in Amitabh Ghosh’s the Shadow Lines (Butwal Campus Journal, 2022)
Amitabh Ghosh’s The Shadow Lines posits the idea of nationalism which was a matter of full-fledged discussion during the post partition India. This article undertakes and examines the characterization of the violent events in The Shadow Lines, concentrating on the traumatic life of the characters and the violence to analyze and evaluate the fundamental causes. Ghosh’s implication in the novel is that the superficial concept of national identity is a root cause of pervasive violence. The researcher claims that Ghosh backgrounds the identities created by the arbitrarily drawn demarcations of national boundaries and desires for the unified identity, a new and distinctive whole created from fusion of different cultures, ethnicities and nationalities as a solution to prevent the recurrence of insane frenzies and communal violence in the era of modern diversity, interconnectedness and globalization.